감미단백질 관련 브라제인, 타우마틴 및 미라쿨린 유전자를 이용한 형질전환 상추 육성 및 발현분석 - 정여진(Yeo Jin Jung); 강권규(Kwon Kyoo Kang) (Journal of plant biotechnology, 2018)
Sweetener is one of the additives that makes you feel sweet. Artificial sweeteners and sugar are typical examples, and sweetness proteins with sweetness characteristics have been widely studied. These studies elucidated the transformation lettuce cells with Agrobacterium method for stable production of natural sweet proteins, brazzein, thaumatin, and miraculin. In this paper, we report use of a plant expression system for production of sweet proteins. A synthetic gene encoding sweet proteins was placed under the control of constitutive promoters and transferred to lettuce. High and genetically stable expression of sweetener was confirmed in leaves by RT-PCR and Western blot analysis. Sweet proteins expressed in transgenic lettuce had sweetness-inducing activity. Results demonstrate recombinant sweet proteins correctly processed in transgenic lettuce plants, and that this production system could be a viable alternative to production from the native plant. 감미료(sweetener)는 단맛을 느끼게 하는 첨가물 중 하나로 인공감미료와 설탕이 대표적이며, 단맛의 특성을 지닌 감미 단백질도 잘 알려져 있다. 본 연구는 천연 감미 단백질, brazzein, thaumatin 및 miraculin의 안정적인 생산을 위해 Agrobacterium방법으로 상추 세포를 형질 전환시켰다. 감미 단백질을 코딩하는 합성 유전자들은 상시적으로 발현하는 프로모터의 제어 하에 상추에 형질전환 하였다. 형질전환한 잎을 이용하여 RT-PCR 및 Western blot 분석을 실시한 결과 감미 단백질이 안정적으로 발현하는 것을 확인하였다. 형질전환 상추에서 발현한 단백질은 단맛을 유발하는 단백질 활성을 가지고 있었다. 이러한 결과는 유전자 재조합 감미 단백질들은 형질전환한 상추에 잘 발현된 것을 보여 주며, 이들 생산 시스템은 식물로부터 감미단백질 생산을 위한 좋은 대안이 될 수 있을 것으로 생각된다.